Quercetin Suppresses the Migration and Invasion in Human Colon Cancer Caco-2 Cells Through Regulating Toll-like Receptor 4/Nuclear Factor-kappa B Pathway - Han, Mingyang (Pharmacogn Mag, 2016)
OBJECTIVE: The migration and invasion features, which were associated with inflammatory response, acted as vital roles in the development of colon cancer. Quercetin, a bioflavonoid compound, was widely spread in vegetables and fruits. Although quercetin exerts antioxidant and anticancer activities, the molecular signaling pathways in human colon cancer cells remain unclear. Hence, the present study was conducted to investigate the suppression of quercetin on migratory and invasive activity of colon cancer and the underlying mechanism. MATERIALS AND METHODS: The effect of quercetin on cell viability, migration, and invasion of Caco-2 cells was analyzed by the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay, wound-healing assay, and transwell chambers assay, respectively. The protein expressions of toll-like receptor 4 (TLR4), nuclear factor-kappa B (NF-κB) p65, mitochondrial membrane potential-2 (MMP-2), and MMP-9 were detected by Western blot assay. The inflammatory factors, such as tumor necrosis factor-α (TNF-α), cyclooxygenase-2 (Cox-2), and interleukin-6 (IL-6), in cell supernatant were detected by enzyme-linked immunosorbent assay. RESULTS: The concentration of quercetin <20 μM was chosen for further experiments. Quercetin (5 μM) could remarkably suppress the migratory and invasive capacity of Caco-2 cells. The expressions of metastasis-related proteins of MMP-2, MMP-9 were decreased, whereas the expression of E-cadherin protein was increased by quercetin in a dose-dependent manner. Interestingly, the anti-TLR4 (2 μg) antibody or pyrrolidine dithiocarbamate (PDTC; 1 μM) could affect the inhibition of quercetin on cell migration and invasion, as well as the protein expressions of MMP-2, MMP-9, E-cadherin, TLR4, and NF-κB p65. In addition, quercetin could reduce the inflammation factors production of TNF-α, Cox-2, and IL-6. CONCLUSION: The findings suggested for the 1(st) time that quercetin might exert its anticolon cancer activity via the TLR4- and/or NF-κB-mediated signaling pathway. SUMMARY: Quercetin could remarkably suppress the migratory and invasive capacity of Caco-2 cells. The expressions of metastasis-related proteins of mitochondrial membrane potential-2 (MMP-2), MMP-9 were decreased, whereas the expression of E-cadherin protein was increased by quercetin in a dose-dependent manner. The anti-toll-like receptor 4 (TLR4) antibody or pyrrolidine dithiocarbamate affected the inhibition of quercetin on cell migration and invasion, as well as the protein expressions of MMP-2, MMP-9, E-cadherin, TLR4, and nuclear factor-kappa B p65. Quercetin could reduce the inflammation factors production of tumor necrosis factors-α, cyclooxygenase-2, and interleukin-6. . Abbreviations used: MTT: 3-(4,5-dimethylthiazol-2-yl)- 2,5-diphen yltetrazolium bromide, TLR4: Toll-like receptor 4, NF-κB: Nuclear factor-kappa B, MMP-2: Mitochondrial membrane potential-2, MMP-9: Mitochondrial membrane potential-9, TNF-α: Tumor necrosis factor-α, Cox-2: Cyclooxygenase-2, IL-6: Interleukin-6, ELISA: Enzyme-linked immunosorbent assay, PDTC: Pyrrolidine dithiocarbamate, ROS: Reactive oxygen species, DMSO: Dimethyl sulfoxide, FBS: Fetal bovine serum, DMEM: Dulbecco modified Eagle medium, OD: Optical density, IPP: Image Pro-plus, PBS: Phosphate buffered saline, SD: Standard deviation, ANOVA: One-way analysis of variance, SPSS: Statistical Package for the Social Sciences, ECM: Extracellular matrix, TLRs: Toll-like receptors, LPS: Lipopolysaccharide.